A nile red-based near-infrared fluorescent probe for endogenous hydrogen polysulfides in living cells. Issue 45 (9th November 2017) - Li, Kai-Bin; Chen, Feng-Zao; Zhang, Siqi; Shi, Wei; Han, De-Man; Cai, Chen; Chen, Cai-Xia
Abstract : Endogenous hydrogen polysulfides (H2 S n ; n > 1) have attracted increasing attention because emerging studies have shown that it is actually the key signaling molecule rather than hydrogen sulfide (H2 S). Abstract : Endogenous hydrogen polysulfides (H2 S n ; n > 1) have attracted increasing attention because emerging studies have shown that it is actually the key signaling molecule rather than hydrogen sulfide (H2 S). Therefore, developing probes for selective and sensitive detection of hydrogen polysulfides is of great significance in biological science. In this study, a new fluorescent off–on probe for the selective and sensitive detection of hydrogen polysulfides (H2 S n ) with near-infrared (NIR) fluorescent signal change has been designed and synthesized. The probe was synthesized by an esterification reaction coupling between a nile red dye and a bis-electrophilic H2 S n capture group 2-fluoro-5-nitrobenzoic acid. The probe showed a specific off–on response to H2 S n in aqueous solution with nanomolar LOD without interference by a range of competing sulfocompounds and several reactive nitrogen and oxygen species. Moreover, it can be used for imaging of endogenous H2 S n in living cells.